2013
DOI: 10.1099/vir.0.053256-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and bioinformatic evidence that raspberry leaf blotch emaravirus P4 is a movement protein of the 30K superfamily

Abstract: Emaravirus is a recently described genus of negative-strand RNA plant viruses. Emaravirus P4 protein localizes to plasmodesmata, suggesting that it could be a viral movement protein (MP). In the current study, we showed that the P4 protein of raspberry leaf blotch emaravirus (RLBV) rescued the cell-to-cell movement of a defective potato virus X (PVX) that had a deletion mutation in the triple gene block 1 movement-associated protein. This demonstrated that RLBV P4 is a functional MP. Sequence analyses revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 55 publications
3
58
0
1
Order By: Relevance
“…The P4 proteins of FMV and RLBV have been demonstrated to be involved in cell-to-cell movement (39,40). Based on sequence homology with other emaraviral P4 proteins, it is likely that the P4 of WMoV might also be involved in cell-to-cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…The P4 proteins of FMV and RLBV have been demonstrated to be involved in cell-to-cell movement (39,40). Based on sequence homology with other emaraviral P4 proteins, it is likely that the P4 of WMoV might also be involved in cell-to-cell movement.…”
Section: Discussionmentioning
confidence: 99%
“…A database search showed the highest identity of this polypeptide with those encoded by RNA4 of FMV (75 %) and RRV (61.2 %) ( Table 2). The SLP-Local (Subcellular Location Predictor) program predicted the expression product of RNA4 to be a possible membrane-located protein lacking the transmembrane helices that are likely to be involved in virus cell-to-cell movement, similar to comparable movement proteins encoded by FMV, PPSMV-1, RLBV, WMoV and RRV RNA4 [8,9,15,31,40,42]. However, this segment contained a conserved motif (FDPNFQQFITGSL 148-160 ), whose function is unknown.…”
Section: Deep Sequencing and Genome Analysismentioning
confidence: 97%
“…2b). This result suggested that p29 associated with PD similarly to other viral MPs [44,[49][50][51][52][53]. Therefore, it was concluded that the p29 protein is most likely involved in the cell-to-cell movement of PepRSV.…”
Section: Pepper Ringspot Virus (Peprsv) Is a Member Of The Genusmentioning
confidence: 80%
“…Moderately conserved sequences ( Fig. 1, blue boxes) were also seen throughout the MPs, with high similarity scores (by aa change within the same aa class) [34,35,44]. The 30K superfamily MPs contain two hydrophobic regions that form an a-helix structure (aa 61-80 and 148-167, Fig.…”
Section: Pepper Ringspot Virus (Peprsv) Is a Member Of The Genusmentioning
confidence: 98%